Analisis Dampak Permainan Problematika Sains terhadap Kecakapan Proses Sains Anak Umur 5—6 Tahun - Yossie Setyo Wardhani; Sri Wahyuni; Ach. Rasyad (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This research was conducted at Dharma Wanita Persatuan 1 TK Senggreng with the purpose of describing the influence of the game of science problems on children's science process skills and describing the differences in the influence from skills of science process for children aged 5—6 years on the treatment of science problematic games and conventional learning methods. This study used a quasy experiment research design that applied the pretest posttest control group a design with quantitative research methods. The results of this research indicate that the mean posttest data score of science process proficiency in the experimental class is 16.00 and is greater than the control class which is 6.10 or 16.00> 6.10. So, there are differences in the effect of science problematics games with conventional learning methods for science process skills in children aged 5 to 6 years.Abstrak: Penelitian ini dilaksanakan dengan tujuan mendeskripsikan dampak permainan problematika sains pada kecakapan proses sains anak serta mendeskripsikan perbedaan pengaruh kecakapan proses sains anak usia 5—6 tahun untuk perlakuan permainan problematika sains dan metode pembelajaran konvensional. Penelitian ini menggunakan rancangan penelitian quasy experiment dengan metode penelitian kuantitatif. Hasil dari riset ini mengindikasikan bahwa nilai rata-rata data postes kecakapan proses sains kelas eksperimen adalah 16,00 dan lebih besar daripada kelas kontrol yang bernilai 6,10 atau 16,00 > 6,10. Jadi, terdapat perbedaan pengaruh permainan problematika sains dengan pembelajaran metode pembelajaran konvensional untuk kecakapan proses sains pada anak usia 5—6 tahun.